Coeliccia duytan sp. nov. from the Central Highlands of Vietnam (Odonata: Platycnemididae) - Phan, Quoc Toan (Zootaxa, 2017)
Coeliccia duytan sp. nov. (holotype male, from Chu Mom Ray National Park, Kon Tum Province, the Central Highlands of Vietnam, deposited in zoological collection of Duy Tan University) is described based on both sexes. The new species is closely related to C. hayashii Phan & Kompier, 2016 by the extensive rectangular pruinosity on the synthorax but differs in lacking a pale antehumeral stripe, genital ligula with flagella pointed at tip and the shape of cerci.